Arthroscopic Treatment of Scaphoid Pseudoarthrosis without Bone Graft: Is it Really Feasible? - Caloia, Martin F.; Scotti, Diego González; Fernández, Diego L. (Revista Iberoamericana de Cirugía de la Mano, 2020)
Introduction The current management of scaphoid pseudoarthrosis remains controversial, with a failure rate of up to 40% and no “gold standard” treatment. Based on innovative concepts about the osteogenic potential of cells from scaphoid pseudoarthrosis, encouraging results from increased vascularization by radial and ulnar metaphyseal decompression for Kienböck disease therapy and the advantages of minimal surgical trauma provided by percutaneous and arthroscopic techniques, we analyzed prospective outcomes from scaphoid pseudoarthrosis arthroscopic treatment with no bone graft (ATSPsWBG) to determine its feasibility.Materials and Methods Eighty-four non-union scaphoid prospectively treated for ATSPsWBG were evaluated. Patients had, on average, 32.42 years old. The dominant limb was affected in 77.5% of the cases (65 patients). Mean time from injury to surgical intervention was 20.57 months. Twenty-three fractures were initially treated conservatively with orthopedic cast for an average period of 6.3 weeks, including 17 already immobilized at the time of the visit. All patients were grouped according to the classification proposed by the authors (MC & DF), which is based on perioperative studies.Results Bone consolidation was obtained in 77 cases (91.66%) and documented by computed tomography (CT) scans. Seven cases presented no bone consolidation 9 months after the procedure, and four cases required a new surgery. In cystic pseudoarthrosis, the bone defect was filled with a new bone growth even when the cyst exceeded 10 mm. Single photon emission computerized tomography (SPECT) scans revealed an unique pattern, documenting the biological effect of metaphyseal decompression, which is characterized by increased nonspecific irrigation of the radial column. Average postoperative pain assessed using the visual analog scale was 1.04 (range, 0 to 2). Average postoperative functional range was 65.3° for extension (range, 46° to 88°), 69.2° for flexion (range, 55° to 88°), 10.7° for radial deviation (range, 5° to 20°) and 26° for ulnar deviation (range, 20° to 37°). Average Mayo Clinic score was 95.Conclusion The arthroscopic treatment of scaphoid pseudoarthrosis with no bone graft is recommended in young to middle-aged, non-smokers patients with no scaphoid consolidation, with hemorrhagic peteqchiae (arthroscopic Green’s Sign) at the arthroscopic evaluation and in which a CT scan excluded the presence of an excessive sclerosis focus or revealed a very small proximal bone fragment not suitable for screw placement for stable internal fixation. Our experience proved that this is a reproducible and feasible technique.Level of Evidence IV
Keywords: scaphoid pseudoarthrosis; wrist arthroscopy; without bone graft; metaphyseal decompression